INFLUENCE OF PULMONARY HYPERTENSION ON CLINICAL COURSE AND PROGNOSIS OF PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - S. N. Avdeev; V. V. Gajnitdinova; N. A. Tsareva; Z. М. Merzhoeva (Российский кардиологический журнал)
Aim. Evaluation of clinical specifics, predictors of repeat hospitalizations and mortality in chronic obstructive pulmonary disease (COPD) patients according to pulmonary hypertension (PH) severity grade.Material and methods. To the study, 288 COPD patients included (II-IV severity grade, GOLD 2016; males 276, females 12; mean age 59,5±9,27 y. o., smoking 23,1±11,42 pack/years; 2,4±0,89 exacerbations annually, body mass index (BMI) 27,2±12,06 kg/m2). According to the presence and grade of systolic pressure increase in pulmonary artery (SPPA) the patients were selected to three groups: 1st — with no PH (SPPA <40 mmHg, n=168), 2nd — with moderate PH (SPPA 40-55 mmHg, n=101), 3rd — with severe PH (SPPA >55 mmHg, n=19).Results. Increase of SPPA was found in 120 (41,7%) patients: moderate PA — in 101 (35,1%), severe PH — 19 (6,6%). It was shown that the presence and severity of PH do increase the severity of clinical signs of COPD, hemodynamic disorders, increase the rate of repeat hospitalizations and mortality rate. The predictors of repeat hospitalizations in COPD patients are increased SPPA and C-reactive protein concentration (CRP); mortality predictors are severity of symptoms by CAT, Borg dyspnea, number of exacerbations during one year, size of the right atrium, grade of SPPA increase, CRP concentration, fibrinogen, N-terminal precursors of C-natriuretic peptide (NT-proCNP) and brain peptide (NT-proBNP) in the blood.Conclusion. PH in COPD patients in most cases is moderate, and it worsens the clinical picture, hemodynamic disorders, shows only moderate correlation with breathing disorders, increases the rate of rehospitalizations and mortality risk. The survival rate of COPD and PH patients depends on the severity.